2015
DOI: 10.1016/j.bbrep.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic remodeling in human colorectal cancer and surrounding tissues: alterations in regulation of mitochondrial respiration and metabolic fluxes

Abstract: The aim of the work was to evaluate whether or not there is glycolytic reprogramming in the neighboring cells of colorectal cancer (CRC). Using postoperative material we have compared the functional capacity of oxidative phosphorylation (OXPHOS) in CRC cells, their glycolytic activity and their inclination to aerobic glycolysis, with those of the surrounding and healthy colon tissue cells. Experiments showed that human CRC cannot be considered a hypoxic tumor, since the malignancy itself and cells surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 118 publications
5
89
0
Order By: Relevance
“…We have recently demonstrated that the mitochondrial VDAC, a binding partner for HK2, was overexpressed in HCC tissue. An increased binding of hexokinase to mitochondria may be responsible for elevated rates of aerobic glycolysis in HCC cells (Chekulayev et al 2015). The presence of mitochondrially-bound HK2 was also revealed in cultured Caco-2 cells (Fig.…”
Section: Coupling Of Oxphos With Hk-catalyzed Reactionsmentioning
confidence: 82%
See 4 more Smart Citations
“…We have recently demonstrated that the mitochondrial VDAC, a binding partner for HK2, was overexpressed in HCC tissue. An increased binding of hexokinase to mitochondria may be responsible for elevated rates of aerobic glycolysis in HCC cells (Chekulayev et al 2015). The presence of mitochondrially-bound HK2 was also revealed in cultured Caco-2 cells (Fig.…”
Section: Coupling Of Oxphos With Hk-catalyzed Reactionsmentioning
confidence: 82%
“…Our study was approved by the Medical Research Ethics Committee (National Institute for Health Development, Tallinn) and it was in full accordance with Helsinki Declaration and Convention of the Council of Europe on Human Rights and Biomedicine. Normal colon tissue samples were controlled for the presence of malignant cells; they were normal according to histopathology and cytochemical studies (Chekulayev et al 2015). Immediately after the surgery, the excised tissues were placed into precooled medium-A.…”
Section: Clinical Materials Patients Preparation Of Tissue Samples Amentioning
confidence: 99%
See 3 more Smart Citations